Efforts to Reduce Stunting Rates among Children in Sambik Bangkol Village - Hazraini, Holida Hana; Ningsih, Desi Afriani; Rosa, Millinia; Musliana, Liza; Nurmawadi, Nurmawadi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
STKIP Hamzar Real Work Lecture (KKN) in Sambik Bangkol Village, which aims to instill awareness among residents, especially parents, to work together to reduce the stunting rate in Sambik Bangkol Village. Stunting is a child's growth problem which can be seen from the lack of nutrition that the child receives. In this case, we conducted observations and interviews as researchers to obtain information related to this stunting problem with several sources from the health administrators for children under five in the village or what are usually called administrators in the posyandu program. This stunting is usually caused by maternal negligence when pregnant who does not pay attention to diet. In terms of health, it is usually referred to as mothers who experience (keks) or nutritional deficiencies during pregnancy. As for other problems, stunting usually occurs among families who are considered economically disadvantaged. The impact of stunting can be seen from the child's growth, such as weight, height, children's health and thinking patterns.